Summer drought alters carbon allocation to roots and root respiration in mountain grassland. Issue 3 (10th November 2014) - Hasibeder, Roland; Fuchslueger, Lucia; Richter, Andreas; Bahn, Michael
Summary: Drought affects the carbon (C) source and sink activities of plant organs, with potential consequences for belowground C allocation, a key process of the terrestrial C cycle. The responses of belowground C allocation dynamics to drought are so far poorly understood. We combined experimental rain exclusion with 13 C pulse labelling in a mountain meadow to analyse the effects of summer drought on the dynamics of belowground allocation of recently assimilated C and how it is partitioned among different carbohydrate pools and root respiration. Severe soil moisture deficit decreased the ecosystem C uptake and the amounts and velocity of C allocated from shoots to roots. However, the proportion of recently assimilated C translocated belowground remained unaffected by drought. Reduced root respiration, reflecting reduced C demand under drought, was increasingly sustained by C reserves, whilst recent assimilates were preferentially allocated to root storage and an enlarged pool of osmotically active compounds. Our results indicate that under drought conditions the usage of recent photosynthates is shifted from metabolic activity to osmotic adjustment and storage compounds.